WUJUD ARSITEKTURAL RUMAH TRADISIONAL DURI ASLI DI KABUPATEN ENREKANG - AS, Zulkarnain (Nature : National Academic Journal of Architecture, 2015)
The rapid advancement of information and communication technologies, as well as cultural interaction networks have an impact on traditional architecture Duri in South Sulawesi. Duri embodiment of the traditional architecture of the original changes were feared to reduce and eliminate the authenticity, uniqueness and beauty. The research objective was to explain the architectural form of the traditional house Duri. Data derived from the results of interviews with 13 people, using the techniques of observation and indepth. Purposive sampling and data analysis techniques and architectural matrix of frequency tabulation. Results showed that the architectural form of the traditional house Duri is equally strong tendency to traditional architecture Bugis and Toraja traditional architecture.